Effect of automated airflow regulation on indirect solar dryer performance: comparative study - Louay Abdulsalam Alkahdery; Aleksey V. Yurchenko; Jamal A.-K. Mohammed; Nikita V. Ershov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Due to its intense summer heat and abundant harvest season, Iraq depends on sun drying to preserve crops. However, intense sunlight can lead to superficial drying, masking internal moisture. Inefficient heating disrupts mass transfer, hindering drying. Consistent air circulation and temperature are vital. Automated control systems can manage these factors, optimizing drying in diverse conditions, reducing energy consumption, and obtaining a high-quality product. Aim. To study the performance improvement of the indirect solar dryer using phase change material as a thermal storage under variable flow rate via automatic control. Methods. Indirect solar dryer combined with phase change material under an automatic control system for drying agricultural products. Results. The authors have conducted comparative study on the performance of an indirect solar dryer that uses a solar air heater with a phase change material as a thermal energy store. The solar dryer was tested for drying agricultural products in Baghdad, Iraq, under two cases of airflow: constant flow rate and automated flow rate control. The authors analyzed such parameters as solar radiation, difference of air temperature across the heater, heater thermal efficiency, drying efficiency, and phase change material freezing time. The phase change material stores thermal energy during the day, releasing it after dusk to run the dryer for 5–6 hours in the case of constant flow and 8–9 hours in the case of automated airflow. The results showed a 15% increase in average drying efficiency and 31% in average collector efficiency under automatically controlled airflow compared to constant airflow.